LOOKIN’ GOOD: LUDIC LOCALIZATION QUALITY ASSESSMENT FOR VIDEO GAMES - Luthfie Arguby Purnomo (Leksema: Jurnal Bahasa dan Sastra, 2025)
Localization quality assessment (LQA) for video games tends to be discriminated in a sense that the assessment rubrics are not solely designed to address the issues of video game localization – the rubrics are generally employed for software or apps in common. Addressing this issue, I constructed an LQA that I called ludic LQA. Five steps were taken in constructing the LQA with participant-oriented research by Saldanha and O’Brien (2014) and participant observation by Spradley (2016) as the research frameworks. First, I investigated cases of LQA from a corpus of games to enlist common problems of localization that influence its quality. Second, employing the theories of schematic network by Tuggy (2006), Baconian perspectives of bias by Walton (1999), prosthetic communication in games by Purnomo et al. (2019), and diegetic and nondiegetic strategies in game localization by Purnomo and Purnama (2019), I constructed the parameters and their parametric weights. Third, I held a focus group discussion (FGD) with a game studio to reveal the applicability of the parameters. Fourth, I implemented the constructed LQA in video game localization (VGL) class to uncover practical issues with real localization problems as the objects of assessment. Fifth, practical issues found in the implementation were implemented in the final design of ludic LQA. Through these steps, ludic LQA was constructed. This LQA has linguistic meanings, cultural references, and spatial constraints. Since this LQA was solely designed for video games, game developers and localization specialists can employ the LQA to generate a thorough and comprehensive quality assessment.